Hindu scriptural value system and the economic development of India - "Sharma, Arvind" (New Delhi, 1980)
This book follows from the conviction that there are no exculsively economic problems, there are only problems, which may be understood in terms of 'relevent' or 'non-relevent' factors.
Keywords: Economics